PENGEMBANGAN EMPATI DAN KEPEDULIAN SOSIAL MELALUI PEMBELAJARAN IPS SD - Sri Ilham Nasution; Aisya Shafa Aqilla (STKIP Singkawang, 2025)
The purpose of this study is to develop empathy and social awareness of students through Social Studies (IPS) learning in Elementary Schools (SD). This study uses Literature Study. Qualitative research methods through literature studies. Data analysis techniques with the following steps: collecting data, reducing data, presenting data and verifying data. Sourced from the literature The results of the study are that Social Studies (IPS) Learning has a very important role in developing empathy and social awareness of students at the Elementary School level because IPS learning not only teaches theoretical knowledge, but also becomes an effective means to foster positive social character.